(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
The interview conducted with artist-craftswoman Jessica Costas reveals a journey marked by a practice that challenges the boundaries between art and craft through textile materiality. The artist discusses how her work, grounded in tufted tapestry, incorporates manual gestures into aesthetic elements and reflects on the historical stigmas associated with textile materiality. She also addresses the relationship between gender, symbolic hierarchies, and the subversion of feminine norms. Jessica reflects on her presence on social media, the tension involving artificial intelligence in the arts, and the centrality of sensorial experience in her work. Her nomination for the international LOEWE FOUNDATION Craft Prize 2025, as the only Latin American representative, symbolizes the strength of her production and the recognition of a language that redefines textile art in the contemporary context.